Health impact assessment and climate change: A scoping review - Priska Ammann; Dominik Dietler; Mirko S. Winkler (Elsevier, 2021)
Climate change has various adverse impacts on public health, ranging from heat-related illness to an increased risk of undernutrition in low-income countries. Health impact assessment (HIA) has been advocated as a valuable tool to systematically identify and quantify the effects of climate change on public health and to inform and evaluate the impact of disease-specific adaptation measures as well as health co-benefits of mitigation measures.We conducted a scoping review to map out peer-reviewed literature on HIA in the context of climate change. Web of Science, Scopus and PubMed were searched without language or time restriction. Publications were included in the full text screening that presented or discussed the application of HIA for investigating health impacts of climate change, or associated adaptation and mitigation measures.In total, 76 peer-reviewed publications from 26 countries were included and characterized. There was a paucity of studies on HIA in the context of climate change from low- and middle-income countries. The most investigated climate change effects were related to temperature and air-pollution. Consequently, associated health impacts, such as respiratory or cardiovascular morbidity and mortality, were examined most frequently. Research-driven HIAs with a quantitative methodological approach were the predominant choice to assess health impacts of climate change. Only one in five publications applied a classical step-by-step HIA approach.While quantitative assessment of health impacts associated with climate change seems to be a well established field of research, the few publications applying a step-by-step HIA approach to systematically anticipate potential health impacts of climate change in a given context point at a missed opportunity for strengthening intersectoral collaboration to maximize health (co-) benefits of climate mitigation and adaptation measures. To promote the use of step-by-step HIA in regions that are most affected by climate change, HIA teaching and training efforts are urgently needed.